Senyapan pada Ujaran Bopak dan Gabriella dalam Acara Tonigh Show Net: Studi Psikolinguistik - Rohmatin, Kartika Nur Khozaainah; Nisa, Choirun; Habib, Rahmadina Amalia (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine various forms of silence that occur in Bopak and Gabriella's conversation on the Tonight Show Net program. This type of research is qualitative descriptive research. The data source comes from the Tonight Show Net YouTube channel on the episode Bopak yang Demen, Tapi Malah Dicomblangin ke Desta! The subjects of this study were Bopak and Gabriella as guest stars on the show, and Desta, Hesti, and Dustin as presenters. The research data are utterances containing silence uttered by Bopak and Gabriella. The data collection techniques used were listening and note-taking. At the data analysis stage, the researcher used a descriptive analysis technique by identifying and describing the forms of silence produced by Bopak and Gabriella's utterances on the show, as well as explaining the causes of the silence. The study results showed that in Bopak and Gabriella's speech, silent silences, silences filled with sounds, and silences filled with words were found. The reason for this silence is that the speaker forgets the vocabulary that will be spoken, is not ready for the sentence that will be spoken and is nervous due to confusion about what will be said and also unstable emotions.